Perceived discrimination and stressful life events are associated with cardiovascular risk score in migrant and non-migrant populations: The RODAM study. (1st July 2019) - Chilunga, Felix P.; Boateng, Daniel; Henneman, Peter; Beune, Erik; Requena-Méndez, Ana; Meeks, Karlijn; Smeeth, Liam; Addo, Juliet; Bahendeka, Silver; Danquah, Ina; Schulze, Matthias B.; Klipstein-Grobusch, Kerstin; et al.
Abstract: Background: Psychosocial stress could be an underlying factor for emerging risk of cardiovascular diseases (CVD) in Africans. We assessed the association between psychosocial stress and estimated CVD risk among non-migrant Ghanaians and migrant Ghanaians living in Europe. Methods: Data from the Research on Obesity and Diabetes among African Migrants (RODAM) study, involving 2315 migrant and 1549 non-migrants aged 40–70 years were used for this study. Psychosocial stress included self-reported stress at work and home, recent negative life events and perceived discrimination. CVD risk was estimated using the pooled cohort equations with estimates ≥7.5% over 10 years defining high CVD risk. Adjusted Odds Ratios (AOR) and 95% confidence intervals (95% CI) were calculated by logistic regression with adjustments for socioeconomic status. Results: Prevalence for migrant and non-migrants were; 72.5% and 84.9% for psychosocial stress and 35.9% and 27.4% for high estimated CVD risk. Stress at work and home was not associated with a high estimated CVD risk in either group. Recent negative life events were associated with a high estimated CVD risk in non-migrants only (AOR 1.29, 95%CI 1.02–1.68, p = 0.048). Higher levels of perceived discrimination were associated with a high estimated CVD risk in migrants only (AOR 2.74, 95%CI 1.95–3.86, p < 0.001). Conclusions: Among migrant populations, higher levels of perceived discrimination were associated with a high estimated CVD risk, and this was also true for recent negative life events among non-migrant populations. Further research is needed to identify context specific mechanisms that underlie associations between psychological characteristics and CVD risk. Highlights: Stress at work and home is not associated with estimated CVD risk Perceived discrimination is associated with estimated CVD risk among migrants. Adverse life events are associated with estimated CVD risk among non-migrants.